Družbenopolitično delovanje duhovnika Antona Mrkuna - Hlebanja, Neža (Časopis za zgodovino in narodopisje, 2022)
This article presents the socio-political engagement of the Slovenian priest Anton Mrkun, with particular emphasis on his work with Slovenian emigrants and the period after World War II, when Mrkun himself emigrated to the USA. The article outlines his activities in the parishes where he worked; central to this article is Mrkun’s support for the idea of an independent Slovenian state, for which he was a strong advocate after the Second World War.
Keywords: Anton Mrkun; družbenopolitično delovanje; Mrkun, Anton; Slovene emigrants; Slovene priests; slovenski duhovniki; slovenski izseljenci; socio-political engagement; USA; ZDA